Default-Implied Asset Correlation: Empirical Study for Moroccan companies - Ammari, Mustapha; Lakhnati, Ghizlane (International Journal of Economics and Financial Issues, 2017)
The asset correlation is a key regulatory parameter in the calculation of the capital charge for credit risk under the second Baselagreement. This parameter has been set in a uniform manner for all banking institutions wishing to integrate the Baselframework. However, estimation of the asset correlation has not often been discussed, even though it substantially affects the estimates of the Unexpected Loss. Importantly, it is essential that financial institutions use the appropriate method and data to calculate the asset correlation in order to compute the Unexpected Loss accurately. In this work, we developed the theoretical framework for the calculation of the Default-Implied Asset Correlation. Using the developed model, we calculated the correlation of the assets that was decreasing according to the probability of default. By comparing our model with the Baselmodel, we found a significant difference on the asset correlation value and the regulatory capital coefficient. This resulted in a large Risk-Weighted Assets difference between our model and the Basel Framework. Keywords: Default-Implied Asset Correlation, Credit Risk Modeling, Asymptotic Single Risk Factor. JEL Classifications: G17, G21, G24, G28, G32, G38